A Comparison of Massive Sulphide Deposits Forming at the PACMANUS (Manus Basin, PNG) and Jade (Okinawa Trough, South China Sea) Seafloor Hydrothermal Fields - S Murao; R A. Binns (The Australasian Institute of Mining and Metallurgy, 1995)
The PACMANUS and Jade deposits are two active hydrothermal fields that are forming massive sulphide deposits at the Pacific rim margin. Both are associated with felsic submarine volcanic rocks and both occur in back-arc settings. However, PACMANUS is associated with almost sediment-free dacites and lies on the crest of a volcanic ridge, whereas Jade occurs in a heavily-sedimented tectonic depression associated with a basement of pumiceous rhyolite. The PACMANUS deposit is richer in Cu and Au, and Jade in Pb. Zinc, Ag, As and Sb contents are similar. Sulfide textures at PACMANUS suggest formation of Cu and Zn sulfides by simultaneous double-diffusion involving inwards-moving seawater mixing with outwards-moving hydrothermal fluid. By contrast, at Jade there is a more complex history of formation where initial growth of barite on the sediment surface, probably associated with microbial activity, formed an impervious cap which trapped higher temperature hydrothermal solutions.